(untitled) (EAAE Joint Publishings, 2026)
Our study explores the intricate relationship between architectural design, care, and atmospheric experiences at the intersection of architecture and psychology. Focused on understanding how on-site experiences interact with initial design intentions, we delve into specific aspects of architectural care and atmospheres. In the latter half of the 20th century, the idea of a profound connection between architecture and human well-being gained prominence. Recently, the concept of atmosphere has emphasized the significance of sensory and affective experiences in places, highlighting the empathic link between the body and the built environment. In this article, we investigate how atmosphere studies and empathy illuminate the connections between architectural care design and on-site experiences, using André Bruyère’s Orb Pavilion as a case study. Through analyzing the architect’s intentions, conducting architectural and sensory on-site analyses, we aim to demonstrate how a design team’s aspirations manifest in the built environment. Our findings underscore the congruence between envisioned aspirations and the on-site experience of the Orb Pavilion, focusing on fostering courtesy, providing supportive care through architecture, and inspiring respect for dignity. We argue that the design team’s dispositional empathy can permeate architecture, highlighting the importance of designers cultivating sensitivity to bodily sensations.